Jean Baudrillard y la publicidad - Caro Almela, Antonio (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2008)
Concerning the dead of the French thinker Jean Baudrillard, this paper pretends to establish a first evaluation of his contributions to the knowledge of the present advertising phenomenon and the framework where it is inserted. This evaluation of Baudrillard’s analysis of advertising confirms the importance of his theoretical work that despite its structuralism roots never abandoned, evolved toward a progressive disenchantment which makes him one of the most radical exponents and remarkable figures of postmodern thinking.